Acute Air Pollution Exposure and the Risk of Violent Behavior in the United States. Issue 6 (November 2019) - Berman, Jesse D.; Burkhardt, Jesse; Bayham, Jude; Carter, Ellison; Wilson, Ander
Abstract : Background: Violence is a leading cause of death and an important public health threat, particularly among adolescents and young adults. However, the environmental causes of violent behavior are not well understood. Emerging evidence suggests exposure to air pollution may be associated with aggressive or impulsive reactions in people. Methods: We applied a two-stage hierarchical time-series model to estimate change in risk of violent and nonviolent criminal behavior associated with short-term air pollution in U.S. counties (2000–2013). We used daily monitoring data for ozone and fine particulate matter (PM2.5 ) from the Environmental Protection Agency and daily crime counts from the Federal Bureau of Investigation. We evaluated the exposure–response relation and assessed differences in risk by community characteristics of poverty, urbanicity, race, and age. Results: Our analysis spans 301 counties in 34 states, representing 86.1 million people and 721, 674 days. Each 10 µg/m 3 change in daily PM2.5 was associated with a 1.17% (95% confidence interval [CI] = 0.90, 1.43) and a 10 ppb change in ozone with a 0.59% (95% CI = 0.41, 0.78) relative risk increase (RRI) for violent crime. However, we observed no risk increase for nonviolent property crime due to PM2.5 (RRI: 0.11%; 95% CI = −0.09, 0.31) or ozone (RRI: −0.05%; 95% CI = −0.22, 0.12). Our results were robust across all community types, except rural regions. Exposure–response curves indicated increased violent crime risk at concentrations below regulatory standards. Conclusions: Our results suggest that short-term changes in ambient air pollution may be associated with a greater risk of violent behavior, regardless of community type. Abstract : Supplemental Digital Content is available in the text.